KECEMASAN BELAJAR MATEMATIKA TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA SMP - Diyah Meily Raniwati; Yuriska Destania (Universitas Muhammadiyah Bengkulu, 2019)
ABSTRACTMathematics has a base object which includes ideas, facts, concepts, principles, and skills with one of the main characteristics of logical reasoning.Â Many students who have difficulty in math, because it requires high mental activity, also claims success in learning mathematics which also determines the continuation of studies at a higher level to make the most of students anxious face of mathematics. This anxiety becomes an important factor to be studied. This study was to determine the relationship of anxiety in mathematics to students' mathematical connection capabilities. Data processed by correlation, the results showed that there was a negative correlation study mathematics anxiety on students' mathematical connection capabilities.Keywords: Anxiety Mathematics, Mathematical Connections